Control of IBMIR in Neonatal Porcine Islet Xenotransplantation in Baboons. Issue 6 (19th May 2014) - Hawthorne, W. J.; Salvaris, E. J.; Phillips, P.; Hawkes, J.; Liuwantara, D.; Burns, H.; Barlow, H.; Stewart, A. B.; Peirce, S. B.; Hu, M.; Lew, A. M.; Robson, S. C.; et al.
<x xml:space="preserve">Abstract</x> The instant blood‐mediated inflammatory reaction (IBMIR) is a major obstacle to the engraftment of intraportal pig islet xenografts in primates. Higher expression of the galactose‐α1, 3‐galactose (αGal) xenoantigen on neonatal islet cell clusters (NICC) than on adult pig islets may provoke a stronger reaction, but this has not been tested in the baboon model. Here, we report that WT pig NICC xenografts triggered profound IBMIR in baboons, with intravascular clotting and graft destruction occurring within hours, which was not prevented by anti‐thrombin treatment. In contrast, IBMIR was minimal when recipients were immunosuppressed with a clinically relevant protocol and transplanted with NICC from αGal‐deficient pigs transgenic for the human complement regulators CD55 and CD59. These genetically modified (GM) NICC were less susceptible to humoral injury in vitro than WT NICC, inducing significantly less complement activation and thrombin generation when incubated with baboon platelet‐poor plasma. Recipients of GM NICC developed a variable anti‐pig antibody response, and examination of the grafts 1 month after transplant revealed significant cell‐mediated rejection, although scattered insulin‐positive cells were still present. Our results indicate that IBMIR can be attenuated in this model, but long‐term graft survival may require more effective immunosuppression or further donor genetic modification.